THE ANALYSIS OF COHESIVE DEVICES IN STUDENTS’ WRITING DISCUSSION TEXT - Nurhaeda Gailea; Syafrizal Syafrizal; Ai Hafipah (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: This study aims to identify the types of cohesive devices, frequency of various types of cohesive devices, how cohesive devices contribute to their texts, find out the students’ problem, and also to know the extent of the cohesion level achieved in the students’s writing of discussion text at SMAN 1 Pandeglang. This study employs qualitative research through a content analysis design. SMAN 1 Pandeglang is chosen as the site for this study. Fiveteen students of twelfth grade are involved in the study as the respondent. The data are analyzed by using the concept of cohesive devices proposed by Halliday (2014) which covers reference, substitution, ellipsis, conjunction, and lexical cohesion. Analyses show that the respondents only use 3 types in the text, i.e.reference, conjunction and lexical cohesion, the most frequent of cohesive devices is about reference that followed by causal conjunction, it is still problematice since they mostly use inappropriate cohesive devices in their writing. As a result, their texts appear to be difficult to understand. Therefore, it is recommended that a students who have to write the text, they should be guided to utilize appropriate cohesive devices in their texts. Keywords: writing, cohesive devices, discussion text